Cardio-Oncology: How New Targeted Cancer Therapies and Precision Medicine Can Inform Cardiovascular Discovery. Issue 23 (8th December 2015) - Bellinger, Andrew M.; Arteaga, Carlos L.; Force, Thomas; Humphreys, Benjamin D.; Demetri, George D.; Druker, Brian J.; Moslehi, Javid J.
Abstract : Cardio-oncology (the cardiovascular care of cancer patients) has developed as a new translational and clinical field based on the expanding repertoire of mechanism-based cancer therapies. Although these therapies have changed the natural course of many cancers, several may also lead to cardiovascular complications. Many new anticancer drugs approved over the past decade are "targeted" kinase inhibitors that interfere with intracellular signaling contributing to tumor progression. Unexpected cardiovascular and cardiometabolic effects of patient treatment with these inhibitors have provided unique insights into the role of kinases in human cardiovascular biology. Today, an ever-expanding number of cancer therapies targeting novel kinases and other specific cellular and metabolic pathways are being developed and tested in oncology clinical trials. Some of these drugs may affect the cardiovascular system in detrimental ways and others perhaps in beneficial ways. We propose that the numerous ongoing oncology clinical trials are an opportunity for closer collaboration between cardiologists and oncologists to study the cardiovascular and cardiometabolic changes caused by the modulation of these pathways in patients. In this regard, cardio-oncology represents an opportunity and a novel platform for basic and translational investigation and can serve as a potential avenue for optimization of anticancer therapies and for cardiovascular research and drug discovery.